2021
DOI: 10.1073/pnas.2111119118
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast synthesis of hard carbon anodes for sodium-ion batteries

Abstract: Hard carbons (HCs) are a significantly promising anode material for alkali metal-ion batteries. However, long calcination time and much energy consumption are required for the traditional fabrication way, resulting in an obstacle for high-throughput synthesis and structure regulation of HCs. Herein, we report an emerging sintering method to rapidly fabricate HCs from different carbon precursors at an ultrafast heating rate (300 to 500 °C min−1) under one minute by a multifield-regulated spark plasma sintering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 40 publications
3
26
1
Order By: Relevance
“…Suitable anode materials are highly demanded in the development of sodium-ion batteries (SIBs) compared to cathodes and electrolytes, since excellent materials are available for the latter. , Numerous studies have revealed a variety of anodic candidates, such as carbons, metal oxides/sulfides, and intermetallic and organic compounds, among which carbon-based materials are reported promising due to their high capacity, structural diversity, and resource sustainability. However, their electrochemical performance needs more improvement to achieve practical applications. The performance of carbon anodes is closely related to the physiochemical properties of Na + ions. For example, partial intercalation reactions due to the large ionic radius (1.02 Å) of the Na + ion not only have disabled graphite’s utilization in SIBs , but can also (1) slow down the ionic diffusion kinetics, (2) significantly change electrode volume during successive charging/discharging, leading to pulverization of the electrode material and thus making it electrochemically unstable, and (3) hinder the formation of uniform and stable solid electrolyte interfaces (SEIs) …”
Section: Introductionmentioning
confidence: 99%
“…Suitable anode materials are highly demanded in the development of sodium-ion batteries (SIBs) compared to cathodes and electrolytes, since excellent materials are available for the latter. , Numerous studies have revealed a variety of anodic candidates, such as carbons, metal oxides/sulfides, and intermetallic and organic compounds, among which carbon-based materials are reported promising due to their high capacity, structural diversity, and resource sustainability. However, their electrochemical performance needs more improvement to achieve practical applications. The performance of carbon anodes is closely related to the physiochemical properties of Na + ions. For example, partial intercalation reactions due to the large ionic radius (1.02 Å) of the Na + ion not only have disabled graphite’s utilization in SIBs , but can also (1) slow down the ionic diffusion kinetics, (2) significantly change electrode volume during successive charging/discharging, leading to pulverization of the electrode material and thus making it electrochemically unstable, and (3) hinder the formation of uniform and stable solid electrolyte interfaces (SEIs) …”
Section: Introductionmentioning
confidence: 99%
“…The features of the as-designed Sn-MnO@C were further confirmed by the long cycling test, in which an average high capacity of 214 mAh g –1 was obtained in the initial 500 cycles at the high current density of 1.0 A g –1 (Figures d and e). These performances are superior to those of most Sn-based and hard-carbon-based anodes previously reported (see Figure f, as well as Figure S4 in the Supporting Information), demonstrating the advantages of the as-designed Sn-MnO@C in storing sodium.…”
mentioning
confidence: 63%
“…[ 47 ] Recently, Zhen et al reported an SPS method ( Figure a), which combines plasma activation, hot pressing, and Joule heating to achieve a heating rate of 300–500 K min −1 . [ 48 ] The hot pressing compressed various carbon precursors, such as sucrose, fructose, and glucose, under high pressure (20 MPa). Then, Joule heating at 1373 K between 1 and 0 min was applied to convert them to hard carbon with fewer defects, lower porosity, and less O content than traditional heating methods.…”
Section: Carbon Structuresmentioning
confidence: 99%